Comparing the immunogenicity of glycosidase-directed resiquimod prodrugs mediated by cancer cell metabolism - Ryan Austin T; Pulukuri Anunay J; Davaritouchaee Maryam; Abbasi Armina; Hendricksen Aaron T; Opp Larissa K; Burt Anthony J; Nielsen Amy E; Mancini Rock J (Acta Pharmacologica Sinica, 2020)
We have recently developed an enzyme-directed immunostimulant (EDI) prodrug motif, which is metabolized to active immunostimulant by cancer cells and, following drug efflux, activates nearby immune cells, resulting in immunogenicity. In this study, we synthesized several EDI prodrugs featuring an imidazoquinoline immunostimulant resiquimod (a Toll-like receptor 7/8 agonist) covalently modified with glycosidase enzyme-directing groups selected from substrates of β-glucuronidase, α- mannosidase, or β-galactosidase. We compared the glycosidase-dependent immunogenicity elicited by each EDI in RAW-Blue macrophages following conversion to active immunostimulant by complementary glycosidase. At a cellular level, we examined EDI metabolism across three cancer cell lines (B16 melanoma, TC2 prostate, and 4T1 breast cancer). Comparing the relative immunogenicity elicited by each EDI/cancer cell combination, we found that B16 cells produced the highest EDI prodrug immunogenicity, achieving >95% of that elicited by unmodified resiquimod, followed by TC2 and 4T1 cells (40% and 30%, respectively). Immunogenicity elicited was comparable for a given cell type and independent of the glycosidase substrate in the EDIs or differences in functional glycosidase activity between cell lines. Measuring drug efflux of the immunostimulant payload and efflux protein expression revealed that EDI/cancer cell-mediated immunogenicity was governed by efflux potential of the cancer cells. We determined that, following EDI conversion, immunostimulant efflux occurred through both P-glycoprotein-dependent and P-glycoprotein-independent transport mechanisms. Overall, this study highlights the broad ability of EDIs to couple immunogenicity to the metabolism of many cancers that exhibit drug efflux and suggests that designing future generations of EDIs with immunostimulant payloads that are optimized for drug efflux could be particularly beneficial.